Pendampingan Program Literasi Dan Numerasi Di Smp IT Al-Inabah Ponorogo Tahun 2022 - Dhafa Al Rochim; Fitra Awalia Rahmawati; Defi Firmansah; Fadhilah Akbar Adayana Tsani (Pengelola Jurnal Politeknik Negeri Ketapang, 2023)
The Literacy Program as a community service activity is part of the Teaching Campus Program Batch 4 of 2022. As a form of implementing Merdeka Belajar, the deployment of students to predetermined schools is intended to help the learning process in schools. The object of this activity is students of SMP IT AL-INABAH PONOROGO which is located at Jl. Harapan Jaya, Japan, Babadan District, Ponorogo Regency, East Java. The method of implementing service, through making means based on student creativity, to be taught to students. The literacy and numeracy improvement program is one of the branches of the interests of Technology Adaptation, improving Administeration, and assisting the school in the teaching process. The result of this service activity is the implementation of several activities that are integrated with Literacy and Numeracy, namely as follows: Procurement of reading gardens, reading corners, traditional dance training, hygiene guard training, and Joyfull Learning activities. The objectivesof the above activities are to foster empathy and social sensitivity, improve skills in thinking and cooperation between teachers and students, develop knowledge, identity, and student skills, increase the role and real contribution of universities and students in national development .